Acúmulo de matéria seca e de nutrientes na cultura do milho verde - Moreira, Jeiza Costa (Universidade Federal Rural do Semi-Árido, 2015)
Knowledge of a crop's growth rate and nutrient accumulation rate is very important for establishing a program of split applications of the recommended total nutrient rates. This study aimed to measure the rate of accumulation and export of dry matter and nutrients by a corn hybrid irrigated under the climatic conditions of the Apodi Plateau. An experiment was carried out in the field in the town of Quixeré, Ceará, Brazil, using the cultivar AG 1051. Ten treatments were applied, resulting from combinations between five rates of N (0, 45, 90, 160 and 220 kg ha-1) and four rates of P2O5 (0, 40, 80, and 120 kg ha-1). The experimental design was a randomized complete block with four replications. In this experiment, a benchmark treatment was chosen (90 kg ha-1 of N + 40 kg ha-1 of P2O5) for completion of sampling. The plants were sampled at 26, 33, 39, 47, 53, 61 and 71 days after sowing, and cut at ground level for evaluation of shoots. Ear and straw were separated at harvest. The following characteristics were evaluated: plant height, stem diameter and accumulation of N, P, K, Ca, Mg, S, B and Zn in the shoots. At the time of harvest at 71 days after sowing (DAS), the levels of these nutrients were also evaluated separately in the ear and in the remainder of the shoot of the plants. Stem diameter showed maximum value at 45 days after sowing (DAS); plant height showed a higher value at the end of the growing period, at 71 DAS. Accumulation of fresh and dry matter, nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, boron and zinc showed higher values at 71 DAS. At the time of harvest, the descending order of nutrient accumulation in the shoots was: potassium > nitrogen > calcium > sulfur > phosphorus > magnesium > zinc > boron. In the ear, this order was: potassium > nitrogen > phosphorus > calcium > magnesium > sulfur > zinc > boron
Accumulation of dry matter and nutrients in sweetcorn crops
Keywords: Zea mays L.; Exportação de nutrientes; Fitomassa; Zea mays L.; Nutrient export; Phytomass; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA